-2x+17=-x+5-4

Simple and best practice solution for -2x+17=-x+5-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+17=-x+5-4 equation:


Simplifying
-2x + 17 = -1x + 5 + -4

Reorder the terms:
17 + -2x = -1x + 5 + -4

Reorder the terms:
17 + -2x = 5 + -4 + -1x

Combine like terms: 5 + -4 = 1
17 + -2x = 1 + -1x

Solving
17 + -2x = 1 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
17 + -2x + x = 1 + -1x + x

Combine like terms: -2x + x = -1x
17 + -1x = 1 + -1x + x

Combine like terms: -1x + x = 0
17 + -1x = 1 + 0
17 + -1x = 1

Add '-17' to each side of the equation.
17 + -17 + -1x = 1 + -17

Combine like terms: 17 + -17 = 0
0 + -1x = 1 + -17
-1x = 1 + -17

Combine like terms: 1 + -17 = -16
-1x = -16

Divide each side by '-1'.
x = 16

Simplifying
x = 16

See similar equations:

| 5.5(x-4)=-.5x+14 | | 2-5s=-11 | | 71-3x=7x-21 | | 2358=287+5x | | (2x-1)(3x+4)=2 | | 59-7x=2x+18 | | 3y+12=3y | | 9x-2(4x+5)=32 | | x+x+2+x+4=147 | | -0.6=-3 | | =3a+7b+4+7a | | -6=x-(3-4x) | | 3x-8=-23 | | 3x+23=11x-49 | | -6a+11=-22 | | 8h-9=8h | | 3(-14+2)=13 | | 4x-30=2x+20 | | =8x+y+4x+2y | | 8s+6=54 | | -5,3/4=-2,1/2(m) | | -4.8f+9=-5 | | 3x+5=2x-2 | | 3p-200=200-2p | | x+50x=220 | | 4(2n+9)+15n=30n-6 | | x-143+512=745 | | (x+6)(x-9)=-14 | | 4x=3x-1+5+2x | | =x+3y+12+5y | | 2/3-9=6-2/3 | | -2p+(8p-6)=-18 |

Equations solver categories